Stressor-Specific Microbiota Intervention - Chuang, Jie-Yu (Frontiers in Nutrition, 2022)
To date, mental disorders are diagnosed and treated by subjective judgement of psychiatrists based on diagnostic criteria and treatment guidelines respectively. Mental disorders are heterogeneous illnesses with a substantial treatment-refractory rate. Thus, there is a great need for novel treatment approaches. This article proposes a treatment approach centered on the concept of the gut-brain axis. There is mounting evidence indicating an association between stressors, microbiota, microglia and mental disorders. Stressors might facilitate dysbiosis, inflammation and the occurrence of mental disorders. This novel treatment approach is based on the idea that stressor types instead of the heterogenous psychiatric diagnosis might be closer to the neurobiological underpinnings of mental disorders. First of all, patients with treatment-resistant mental disorders will be asked to describe their major stressors. Then, clinicians will calculate the total threat score and the total deprivation score. Subsequently, treatment tailored to the major stressor type will be administered to restore a healthy gut microbiome. Presumably, treatment will be aimed at increasing microbiota diversity in those who mainly have deprivation stressors and boosting Actinobacteria in those who have mainly threat stressors. Large-scale clinical trials are warranted to test this hypothetical approach.